Cardiac function and intracellular Ca2+ handling proteins are not impaired by high-saturated-fat diet-induced obesity - Deus, A. F. [UNESP]; Vileigas, D. F. [UNESP]; Silva, D. C. T. [UNESP]; Tomasi, L. C. [UNESP]; Campos, D. H. S. [UNESP]; Okoshi, K. [UNESP]; Padovani, C. R. [UNESP]; Cicogna, A. C. [UNESP] (Assoc Bras Divulg Cientifica, 2019)
Obesity is often associated with changes in cardiac function; however, the mechanisms responsible for functional abnormalities have not yet been fully clarified. Considering the lack of information regarding high-saturated-fat diet-induced obesity, heart function, and the proteins involved in myocardial calcium (Ca2+) handling, the aim of this study was to test the hypothesis that this dietary model of obesity leads to cardiac dysfunction resulting from alterations in the regulatory proteins of intracellular Ca2+ homeostasis. Male Wistar rats were distributed into two groups: control (C, n=18; standard diet) and obese (Ob, n=19; high-saturated-fat diet), which were fed for 33 weeks. Cardiac structure and function were evaluated using echocardiographic and isolated papillary muscle analyses. Myocardial protein expressions of sarcoplasmic reticulum Ca2+-ATPase, phospholamban (PLB), PLB serine-16 phosphorylation, PLB threonine-17 phosphorylation, ryanodine receptor, calsequestrin, Na+/Ca2+ exchanger, and L-type Ca2+ channel were assessed by western blot. Obese rats presented 104% increase in the adiposity index (C: 4.5 +/- 1.4 vs Ob: 9.2 +/- 1.5%) and obesity-related comorbidities compared to control rats. The left atrium diameter (C: 5.0 +/- 0.4 vs Ob: 5.5 +/- 0.5 mm) and posterior wall shortening velocity (C: 36.7 +/- 3.4 vs Ob: 41.8 +/- 3.8 mm/s) were higher in the obese group than in the control. The papillary muscle function was similar between the groups at baseline and after inotropic and lusitropic maneuvers. Obesity did not lead to changes in myocardial Ca2+ handling proteins expression. In conclusion, the hypothesis was not confirmed, since the high-saturated-fat diet-induced obese rats did not present cardiac dysfunction or impaired intracellular Ca2+ handling proteins.
Keywords: Obesity; Saturated fatty acids; High-fat diet; Cardiac function; Calcium handling proteins; Rat